IMPROVING STUDENTS’ WRITING ACHIEVEMENT IN THE REPORT TEXT THROUGH FILM - Esra N.F. Hutahaean and Tjut Ernidawati (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2013)
This research concerns on improving students’ writing achievement in the report text through film.  The objective was to find out the improvement of students’ writing achievement in writing the report text through film. This research was conducted by using action research method. The subject of the research was XI IPA grade students of SMA SWASWTA JOSUA Medan. The numbers of students were thirty one students. They were taught writing the report text through film. The instruments used were writing report text test, diary notes, interview sheets, questionnaire sheets and observation sheets. In analyzing data, the mean of students’ score for the first competency test was 43.1, for the second competency test was 64.8 and for the third competency test was 76.3 and the total percentage of improvement from the first competency test to the third competency test was 84.1%. The conclusion is that through watching film can improve the students’ writing achievement in the report text. It is suggested that teachers should apply watching film as one of media to improve students’ writing achievement in the report text.